Developing a multiple glazing system to minimize transmission of direct insolation for particular latitudes - Askar, H. K. (Cranfield University, 2006)
Too often, in the last 50 years, the energy-thrift lessons of vernacular architecture have been forgotten or ignored. In the Middle East, many recently-designed commercial buildings, with large areas of glazing, incur excessively high electricity-demands to provide energy for the required air-conditioning plant. One way of reducing the magnitude of this demand is through better window design. A new glazing system is proposed that utilizes the insertion of a clear glazing element within the cavity of a double glazed window. The main objective of this system is to achieve acceptable levels of daylight within a building by attempting to maintain the diffuse component of insolation while reducing the penetration of direct component by using the increased reflectivity of these materials with the angle of incidence of the direct beam component of solar irradiation. By using clear glazing materials the proposed system attempts to achieve acceptable performance without the need for elaborate and expensive coatings or substrates. Because solar geometry varies with latitude a varying performance of glazing systems is expected with current glazing systems. However, the suggested system utilizes an optimal angle for overall daylighting and thermal performance that relates to the particular solar geometry of interest, New software is also developed to assess the performance of the suggested system; this involved examining all the modes of heat transfer through the entire glazing system. Results then were assessed to calculate the optimal angle of the element that corresponds to the solar geometry of particular latitude. Such proposal takes a new perspective, once it is acknowledged that though different forms of advanced glazing systems currently are being used to inhibit the penetration of direct solar radiation, still the main disadvantages of such advanced glazing systems are that they are relatively expensive and would reduce the penetration of a considerable part of the daylight entering the space.